Exploring Teachers' Strategies for Integrating 21st Century Skills in STEAM - Avanti Vera Risti Pramudyani; Risanti Dhaniaputri; Sujarwo Sujarwo; Mariana Wahyu Listyati; Tanaya Qatrunada Rutriningtyas (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Education has challenges in preparing students with the skills needed in the 21st Century, namely 4C. This ability can be developed with the STEAM approach, which can be implemented from the PAUD level by linking the real world to practical activities in the classroom. Teachers are facilitators in providing play activities, so they need a comprehensive understanding of STEAM. This study aims to see the understanding of teachers at the PAUD level in mastering the STEAM concept both theoretically and practically. This study uses case study research to gain an in-depth understanding of the 4Cs in STEAM Learning based on the teacher's perspective in integrating 21st Century skills. Four teachers participated as key informants with the criteria of alumni from the PGPAUD Study Program before 2000, working for more than 3 years in PAUD institutions, and participating in STEAM-related training. Data collection used research instruments of interviews, observations, and documentation, and was analyzed with thematic analysis using five themes. The study results showed diversity in understanding the STEAM approach to developing 4C skills, but all agreed that using loose parts and projects was easier to integrate. The study's findings found a discourse on the terminology of learning models and approaches. This study has implications for teacher professional development with the hope of increasing pedagogical literacy as a basis for learning.